The role of face (mien-tzu) in Chinese tourists' destination choice and behaviors. (September 2021) - Chen, Li-Hsin; Loverio, Jennifer Pasion; Mei-jung, (Sebrina) Wang; Naipeng, (Tom) Bu; Shen, Ching-Cheng
Abstract: Face, or mien-tzu, has been identified as a crucial sociocultural concept in Chinese society. However, limited research has examined the role of face/ mien-tzu in tourism. This qualitative study fills this void and explores how mien-tzu may be a vital motivation to travel, influencing travel behaviors and destination choices among Chinese tourists. Purposive and snowball sampling techniques were employed to select Chinese tourists with extensive and limited travel experience. In total, 20 participants were interviewed in Weihai and Qingdao, China. The Chinese concept of mien-tzu with the theory of the leisure continuum (1966) and Riley's (1995) prestige-worthy tourism was integrated to guide the analysis. The results indicated that the interviewees would travel to high-tier or prestigious destinations, purchase luxury tourism products, take pictures with famous landmarks, and share travel photos on social media because they believe these behaviors make them "gain face." Additionally, this study also showed that Social Media postings or sharing had blurred the delineation between travel engagement and post-travel. Tourists share their experiences during their travel to inform their circle of friends where they are and what they are doing and savor these memories. This sharing also benefits in making them an expert, allowing them to gain face in their circle. Moreover, this study also found an inherent, implicit characteristic of face. Participants though not admitting face gaining reason for sharing, enjoy the attention and positive feedback from their social media posts and revel in the prestige or face gain conferred by their social circle/network. Theoretically, this study situates Riley's framework in the 21st century. Although the study of Chinese tourists gives it an Eastern point of view, the propensity to post on social media is a trait shared by tourists worldwide. As such, a new framework is proposed and this is the main contribution of this study. This proposed framework can be used in other studies with tourists of different nationalities. The practical implication of this study is for DMOs' to include in their plan a way to provide tourists to create more memories that can be shared on their Social Media. More places where they can take photographs or videos of their experiences can be developed. Providing precious memories that the tourists can continuously share could help in the destinations' promotion because the visitors (tourists) become the de facto expert in their social circle and willing marketers for the destination. Due to the popularity of social media and its influence, the DMO's looking to increase their presence in the Chinese market should include advertising in Chinese Social Media in their plans. Advertising in social media may be a more cost-effective way to advertise and reach more citizens than traditional marketing can.